Unveiling Otolith Mystery: Contemporary Testing Approaches and Their Clinical Significance - Shun Zhou; E Tian; Hua‐Jing Yang; Jun Wang; Zhao‐Qi Guo; Jing‐Yu Chen; Wan‐Di Xu; Jia‐Qi Guo; Zhang‐Hong Zhou; Shi‐Yu Shi; Xi‐Xi Yu; Xin‐Bo Gao; et al. (World Journal of Otorhinolaryngology - Head and Neck Surgery, 2026)
ABSTRACT Objective Otolith is a critical component of the peripheral vestibular system responsible for detecting linear acceleration. Dysfunction of the otolith organs can lead to vertigo, balance disturbances, and gaze instability. By elucidating the physiological foundations and evaluating both current and emerging methods for assessing otolith function, this review aims to provide a comprehensive resource for researchers and clinicians in the field of vestibular science, contributing to improved diagnostic accuracy and the development of more effective therapeutic strategies. Data Sources The databases of PubMed, Embase, and Cochrane Library were systematically searched for the articles. Methods The information of physiological mechanism and clinical significance were extracted from each article. Results Vestibular‐evoked myogenic potentials (VEMPs) are valuable for evaluating saccule and utricle function, with clinical applications in diagnosing several diseases. Subjective visual vertical (SVV) has clinical value in the diagnosis of peripheral and central vestibular diseases, with recent advancements in smartphone Apps and VR devices providing more accessibility. The ocular counter‐roll (OCR) examination has a superior application prospect, but standardization including the normal range and duration of recovery, was incomplete. The off‐vertical axis rotation (OVAR) can be used to explore motion sickness. The test of linear acceleration perception is limited by device, site and result instability, so it is difficult to apply clinically. Balance‐related tests have been applied clinically, but the isolation of otolith components that determine balance is an unfinished task. Conclusion The review emphasizes the need for more precise and standardized otolith function tests to enhance diagnostic accuracy and therapeutic strategies, ultimately improving patient outcomes in vestibular disorders.